Reading the Old Testament as Story: A Pedagogy for Spiritual Formation - Brisben, David (Christian education journal, 2012)
Since the middle of the 20th century, noted Old Testament scholars and theologians like Bernard Anderson, Hans Frei, Craig Bartholomew, and Michael Goheen have raised the concern that the contemporary church not only has lost reading and understanding the Old Testament as story, but that this loss has hindered its spiritual formation. While affirming their concern, qualitative research composed of interviews, narrative descriptions, and questionnaires of 138 college-aged students who largely identify with the Evangelical tradition will be presented showing that when the Old Testament is recovered as story, God is encountered, transformation is experienced, and faith is developed.